Liquid flow process single loop Fuzzy Logic control at Model WF 922: article - Wan Nor, Wan Arifin; Ahmad, Mohd Aizad (2017)
Flow measurement and control are essential in plant process control. The aim of this paper is to study the performance and to find the best input and output signal of Fuzzy Logic controller for flowing fluids. This controller is implemented using DeltaV Fuzzy Control programming, which uses the Fuzzy Logic Control (FLC) function block to provide an advance alternative to standard PID control. During the past several years, fuzzy control has emerged as one of the most active and fruitful areas for research in the applications of fuzzy set theory, especially in the realm of industrial processes, which do not lend themselves to control by conventional methods because of a lack of quantitative data regarding the input-output relations. By using Load Disturbance Test, each setpoint of 1.8, 3.5 and 4.2m3/h liquid, will be having four different parameters of Error (e), Change of Error (Δe), and Change of Output (Δu). The comparative results would be the difference of settling time, Integral Absolute Error (IEA) and decay ratio